2009
DOI: 10.1152/ajpgi.90567.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brain stem cholecystokinin-8s on gastric tone and esophageal-gastric reflex

Abstract: Holmes GM, Tong M, Travagli RA. Effects of brain stem cholecystokinin-8s on gastric tone and esophageal-gastric reflex. Am J Physiol Gastrointest Liver Physiol 296: G621-G631, 2009. First published January 8, 2009 doi:10.1152/ajpgi.90567.2008.-The actions of cholecystokinin (CCK) on gastrointestinal functions occur mainly via paracrine effects on peripheral sensory vagal fibers, which engage vago-vagal brain stem circuits to convey effector responses back to the gastrointestinal tract. Recent evidence suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 78 publications
2
54
0
Order By: Relevance
“…We have previously demonstrated that central administration of CCK-8s to the DVC induces gastric relaxation. Specifically, the gastroinhibitory effect of 450 pmol CCK-8s microinjection into the DVC was eliminated by vagotomy and systemic pretreatment with the nitric oxide synthase inhibitor L-NAME 18. These data demonstrated that the effects of central CCK-8s microinjection are vagally-mediated and include a postganglionic NANC pathway.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We have previously demonstrated that central administration of CCK-8s to the DVC induces gastric relaxation. Specifically, the gastroinhibitory effect of 450 pmol CCK-8s microinjection into the DVC was eliminated by vagotomy and systemic pretreatment with the nitric oxide synthase inhibitor L-NAME 18. These data demonstrated that the effects of central CCK-8s microinjection are vagally-mediated and include a postganglionic NANC pathway.…”
Section: Discussionmentioning
confidence: 72%
“…CCK release has profound effects on gastrointestinal functions 9-11, its vagal mechanisms of action include a paracrine activation of vagal afferent fibers along the gut wall (reviewed in 12) as well as direct actions upon nodose ganglion 13,14, and DVC neurons 15-18.…”
mentioning
confidence: 99%
“…The main support for this mechanism of action derives from the observation that capsaicin treatment, either systemic, perivagal, or directly to the intestinal mucosa, attenuates or abolishes the effects of systemic administration of CCK on functional gastric and pancreatic parameters (33,34,42,46). Behavioral, electrophysiological and pharmacological studies from many groups, including our own, strongly suggest that the effects of CCK may not be limited to a paracrine mechanism of action, however, and effects at other sites, including direct actions on central vagal brainstem circuits, must be considered (5,9,10,16,27,43,56). The second aim of this study was to investigate whether CCK-sensitive afferent inputs to cNTS neurons are, indeed, C-fibers and are therefore responsive to the vanilloid agonist capsaicin but insensitive to purinergic agonists.…”
mentioning
confidence: 72%
“…3). A hormonal effect of CCK on DVC neurons is probable; in rats, brainstem microinjections of CCK8s decrease gastric tone and motility, reduce the gastric response to oesophageal distention (the RRR) 133 and increase pancreatic exocrine secretion 118 . Underestimating the potentially adverse effects of capsaicin on vagal efferent function would, therefore, lead to overestimation of the vagal afferent contribution to the actions of CCK and other gastrointestinal neuropeptides.…”
Section: Gastrointestinal Peptidesmentioning
confidence: 99%